PERLAKUAN AKUNTANSI ATAS PAJAK PERTAMBAHAN NILAI DI KOPERASI PEGAWAI BADAN URUSAN LOGISTIK (KOPEL) - Husadha, Cahyadi; Melviani, Yuliana (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
This study aims to determine the accounting treatment and compliance of deposits of Value Added Tax on the activities of the delivery and the acquisition of Taxable Goods and Taxable Services in the Cooperative Employees Agency Logistics Affairs (KOPEL). This research method using descriptive qualitative analysis method which arranged in accordance with the plan about sale and purchase transactions and SPT Period VAT every month. The results of this study indicate that the Cooperative Employees Agency Logistics Agency (KOPEL) has implemented the recording of Value Added Taxes in 2015 which has been guided by the Financial Accounting Standards (SAK) applicable in Indonesia. Further discussion and research are described in the paper. Keywords: value added tax, accounting compliance